The Relationship Between ESG Factors, Profitability, and Tax Avoidance: A Systematic Literature Review - Yusnidar, Yusnidar; Wahyudi, Tertiaro; Yusnaini, Yusnaini (Jurnal Akuntansi, 2025)
This study examines in depth the various determinants of corporate tax avoidance practices. Exploring the topic of tax avoidance is important because this strategy is recognized and legally permitted in many countries in the world. This study aims to conduct a Systematic Literature Review (SLR) to examine the relationship between Environmental, Social, and Governance (ESG), profitability, and tax avoidance. This article reviews 30 publications published in the period 2015 to 2024 in reputable journals indexed by Scopus. The results of the study provide a comprehensive analysis of the influence of various factors on corporate tax behavior. The findings show that ESG and profitability act as inhibitors of aggressive tax avoidance strategies, as well as being a means to minimize reputational risks due to such practices. ESG and profitability have varying effects on tax avoidance, depending on motives such as efforts to maximize profits, the need for transparency, and ethical considerations. The results show that the independent variables ESG and profitability have a significant relationship with tax avoidance. ESG tends to have a negative effect on tax avoidance, meaning that the better the implementation of ESG, the lower the tendency of companies to avoid taxes. On the contrary, profitability tends to have a positive effect, where increasing profits are often followed by increasing tax avoidance strategies. It is hoped that this article will not only broaden insights in this field, but also trigger further research on other independent variables that are still rarely studied. By closing this gap, future research is expected to be able to provide a deeper understanding of corporate governance and various tax strategies. This journal is expected to be a trigger for innovation in understanding the ethical aspects of corporate decision making, with the aim of supporting more responsible and transparent global business practices.